Review and Update on New Horizon in the Management of Venous Ulcers. (February 2014) - Mousa, Albeir Y.; Richmond, Bryan K.; AbuRahma, Ali F.
Chronic venous ulcers (CVUs) contribute to functional deficits and are a source of significant morbidity among the affected population. In addition, they directly impact the quality of life of patients and are a significant economic burden on the health care system. In this review, we critically evaluate the current strategies for treating CVUs that have emerged within the last decade and outlined a suggested algorithm for treating patients with this difficult condition.